De novo UNC13B mutation identified in a bipolar disorder patient increases a rare exon‐skipping variant - Takumi Nakamura; Kotori Jimbo; Kazuo Nakajima; Takashi Tsuboi; Tadafumi Kato (Wiley, 2018)
Abstract Aim We previously performed the first trio‐based exome study for bipolar disorder and identified 71 de novo mutations. Among these mutations, the only mutation located at the splice donor site was in UNC13B. We focused on and analyzed the functions of the mutation. Methods In order to analyze the functional alterations, due to the mutation, we performed a minigene splicing assay. Key results We found that the mutation caused the loss of a wild‐type splicing variant, which was consistent with the computational splice prediction, and that an exon‐skipping variant increased significantly. The exon‐skipping variant also existed in the wild‐type minigene, although it was rare. Hence, we validated the expression of the exon‐skipping variant using total RNAs derived from the human cerebral cortex. We showed the possibility that the exon‐skipping variant was rare, but expressed even in those that do not carry the mutation. Conclusions Based on our results, we suggest that an abnormal splicing pattern of UNC13B occurred in the patient, which could be related to the pathophysiology of bipolar disorder.